Layanan Dasar dalam Bimbingan dan Konseling di Sekolah - Boy Haryono (Fakultas Agama Islam Universitas Wiralodra, 2026)
Layanan dasar or what is often known as the guidance curriculum in Guidance and Counseling (BK) in schools, is an important part of the program component in schools. This is based on the fact that guidance curriculum provide students with a structured understanding of the reality of life. The purpose of this research is to find out in depth about the concept of guidance curriculum in schools. The research method used is a qualitative method with a literature study approach and data analysis using the Miles and Huberman model. Data collection techniques in this study used relevant sources such as scientific articles, books, proceedings, etc. There are research results that show basic services can be understood as a systematic and planned effort by counseling teachers to students, in order to gain skills and experience and develop self-adjustment abilities to achieve developmental task competencies. Basic services are an integral part of the BK service component at school. The purpose of implementing basic services is so that students have normal self-development, mental health, and achieve self-development tasks. The development of basic services is focused on developing students' self-competence in personal, social, learning and career fields according to developmental levels.